Ethnomedical Perspectives on Visha Dravyas – A Review - B, Soubhaghyalaxmi (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Ethnomedicine, the study of traditional medical practices used by various ethnic groups, often incorporates the use of “Visha Dravyas“ in therapeutic contexts. This review delves into the ethnomedical perspectives on Visha Dravyas, highlighting their historical and contemporary applications, and therapeutic benefits within traditional medical systems such as Ayurveda and indigenous healing practices. Visha Dravyas, despite their inherent toxicity, have been meticulously utilized for their potent medicinal properties, offering treatments for a range of ailments. This dual nature — being both toxic and therapeutic — underscores the sophistication of traditional knowledge systems in balancing harm and healing. Materials and Methods: The review examines key poisonous plants and their pharmacological uses in different regions of India and the world, supported by both traditional texts and modern scientific studies. In addition, the review addresses the cultural and ritualistic aspects of Visha Dravyas, emphasizing the holistic approach of ethnomedical practices that integrate physical, spiritual, and environmental health. Results: This study aims to provide a comprehensive understanding of the role of Visha Dravyas in ethnomedicine. It underscores the importance of preserving traditional knowledge and promoting interdisciplinary research to unlock the full potential of these potent natural resources. Discussion: The findings highlight the need for a nuanced approach to integrating traditional and modern medical practices, ensuring safety and efficacy in the use of Visha Dravyas for future health-care innovations. Conclusion: Review concluded that the use of ethnomedicinal plants increased with elevation due to limited alternative options and market accessibility. Almost all plants contain active components that can be effective against diseases, but certain plants despite being poisonous possess valuable medicinal use.